Atrial tachycardia, atrioventricular conduction disturbance and right heart failure years after removal of a cardiac hydatid cyst. Issue 5 (2017) - Antoniou, Christos–Konstantinos; Arsenos, Petros; Apostolopoulos, Nikos; Dilaveris, Polychronis; Sideris, Skevos; Tsiachris, Dimitris; Skiadas, Ioannis; Sotiropoulos, Elias; Gatzoulis, Konstantinos A.
No abstract available